Simulation of Fretting Fatigue in Conformal and Concentrated Contacts - Dag Fritzson (Japanese Society of Tribologists, 2011)
Fretting fatigue is a possible failure mode of rolling bearings, as well as for other machine elements with contacts. For a rotating bearing it normally can occur in the interfaces between outer ring/housing, and inner ring/shaft. For a non-rotating bearing subjected to small motion due to vibration, it can occur in the concentrated rolling element/ring contacts as well (mainly related to false brinelling). Detailed models for fretting-fatigue have been transferred and adapted to a bearing simulation framework called BEAring Simulation Toolbox (BEAST). It allows the use of the fretting-fatigue model to predict failures and be used by engineers in developing new solutions. Another important usage is to provide a platform for further development of other fretting-fatigue models, fretting-wear and false brinelling models. The results from two different examples are presented; one model with an oscillating body in contact with another, representing a concentrated contact, and one model with a Deep Groove Ball Bearing (DGBB) mounted inside a ring-like housing. Results are presented in terms of contact pressures, shear forces at the surfaces and a parameter representing the fretting risk according to the Dang-Van criterion. The model for the concentrated contact is used to verify the simulations against stand-alone computer code and experiments. The DGBB model shows how the fretting-fatigue related results are influenced by the ball pass frequency and the flexibility of the bearing and the housing.